2018
DOI: 10.1038/s41467-018-06021-7
|View full text |Cite
|
Sign up to set email alerts
|

Restricted cell cycle is essential for clonal evolution and therapeutic resistance of pre-leukemic stem cells

Abstract: Pre-leukemic stem cells (pre-LSCs) give rise to leukemic stem cells through acquisition of additional gene mutations and are an important source of relapse following chemotherapy. We postulated that cell-cycle kinetics of pre-LSCs may be an important determinant of clonal evolution and therapeutic resistance. Using a doxycycline-inducible H2B-GFP transgene in a mouse model of T-cell acute lymphoblastic leukemia to study cell cycle in vivo, we show that self-renewal, clonal evolution and therapeutic resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 56 publications
(82 reference statements)
5
19
0
Order By: Relevance
“…Elimination of LSCs and their ancestral clones, preleukemic stem cells (pre-LSCs), is critical for long-term cure, as they are the source of relapse following chemotherapy [2][3][4] . How these cells survive high-dose chemotherapy remains poorly defined, but may include quiescence and pro-survival signals provided by the microenvironment [5][6][7][8] . To study mechanisms of therapeutic resistance in pre-LSCs, we have utilized the Cd2-Lmo2-transgenic (Lmo2 Tg ) mouse model of T-cell acute lymphoblastic leukemia (T-ALL) 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elimination of LSCs and their ancestral clones, preleukemic stem cells (pre-LSCs), is critical for long-term cure, as they are the source of relapse following chemotherapy [2][3][4] . How these cells survive high-dose chemotherapy remains poorly defined, but may include quiescence and pro-survival signals provided by the microenvironment [5][6][7][8] . To study mechanisms of therapeutic resistance in pre-LSCs, we have utilized the Cd2-Lmo2-transgenic (Lmo2 Tg ) mouse model of T-cell acute lymphoblastic leukemia (T-ALL) 9 .…”
mentioning
confidence: 99%
“…To study mechanisms of therapeutic resistance in pre-LSCs, we have utilized the Cd2-Lmo2-transgenic (Lmo2 Tg ) mouse model of T-cell acute lymphoblastic leukemia (T-ALL) 9 . Using this model, we can identify and purify pre-LSCs with long-term self-renewal and resistance to high-dose therapeutic regimens 5,10 . Given that pre-LSCs harbour some, but not all the genetic lesions found at diagnosis, these cells are more reliant on the signals from the microenvironment to develop, self-renew and clonally evolve 11 .…”
mentioning
confidence: 99%
“…For example, both pharmacological and environmental factors arrested melanoma cells were in G1 phase to be resistant to bortezomib and temozolomide-mediated cytotoxicity [5]. The leukemia stem cells with restricted cell cycle were characteristic of self-renewal, clonal evolution and therapeutic resistance [6]. Si et al showed that EZH2 silencing may reverse tamoxifen resistance in MCF-7 breast cancer cell by regulating the cell cycle [7].…”
Section: Ivyspringmentioning
confidence: 99%
“…Female nude mice (6)(7)(8) week, 18-20 g) were purchased from the Shanghai Laboratory Animal Center. All mice were synchronized with a 12 h light/dark cycle in an autonomous chronobiological animal facility (Suzhou, Jiangsu, China), with the lights on from 6 am (Zeitgeber time 0) to 6 pm (Zeitgeber time 12) for 1 week.…”
Section: Xenograft Tumor Modelmentioning
confidence: 99%
“…It represents a severe and common hematologic malignancy. Because LSCs play a critical role in AL initiation, multidrug resistance and recurrence of leukemia (Bonnet & Dick, 1997; Lapidot et al, 1994; Ratajczak, Bujko, Mack, Kucia, & Ratajczak, 2018; van Rhenen et al, 2007), selectively targeting LSCs has been identified as a promising strategy for leukemia treatment (Baquero et al, 2018; Ding et al, 2016; Guzman et al, 2014; Liu et al, 2013; Tremblay et al, 2018). Here, we provide the first in vitro and in vivo evidence that E35, a novel Emodin derivative, preferentially eradicates AL stem and progenitor cells.…”
Section: Discussionmentioning
confidence: 99%